O conceito de natureza em diferentes ciências - Veltrone, Allan Rogério (2013)
Our purpose is to conduct a discussion about how nature has been conceived by science. Our hypothesis is that science can not be understood as isolated instance, as the scientific description of reality is influenced and influences conceptions of the social context in which it (science) is inserted. To illustrate our point of view, we chose the concept of nature. This concept is confused with the concept of real, appears as human otherness, before which man must stand and merges with a project of society you want to include nature in politics. The discussion humanity x nature has guided the development of western ontology, especially science. Nowadays, the discussion remains, and different scientific fields have been questioning the boundary between the two domains. We will review the work of established authors of the natural and human sciences, which we consider as founders of visions of nature. From there, enter the implications that these approaches have had and for the development of science: for the natural sciences, nature can be fully understood through the impersonal methods of science. However, we believe that science interprets it according to a specific language, and its conclusions are translations of nature, not an accurate description of it. Regarding the human sciences, despite nature does not directly constitute the object of study, we believe that it is present, usually in a manner not spelled out: how ontology is responsible, as opposed to being human, whether as a representation without autonomous existence. We will seek to make it more evident that some concepts of nature permeate the humanities, until we get proposals seeking to question the separation culture x nature. We discuss the nature as a political project, a movement that part of the advent of the scientific concept of ecology, but that is appropriate as a social project.